Back Matter Vol. 1, No. 1, June 2021 - Uktub Journal (The Arabic Education Department Postgraduate Programs, UIN Sultan Maulana Hasanuddin Banten in Partnership with PPJKBA Indonesia, 2021)
Author Guideline Back Cover